2D flakes of Au decorated SnO2 nanoparticles as electrode material for high performing supercapacitor. (18th May 2023) - Anshu, Satvik; Priya, Surbhi; Mandal, Debabrata; Rahul, R; Singh, Trilok; Chandra, Amreesh
Abstract: 2D decorated nanostructures are fast emerging as efficient electrode materials for electrochemical devices. Au decorated SnO2, synthesized using co-precipitation and hydrothermal methods, can become a useful electrode material for supercapacitors. Au incorporation helps to mitigate the conductivity issues of SnO2 nanostructures. The superior 2D-flake like morphology leads to appreciable performance enhancement, with specific capacitance of 234 F g −1 at 1 A g −1 current density, which is much larger than that observed in pristine SnO2 . The high cycling stability of Au-decorated SnO2 clearly shows its usefulness for high-performance supercapacitors. A theoretical model is also reported to explain the electrochemical results.